Evolution of supply chain finance: A comprehensive review and proposed research directions with network clustering analysis. (8th December 2021) - Parida, Ratri; Dash, Manoj Kumar; Kumar, Anil; Zavadskas, Edmundas Kazimieras; Luthra, Sunil; Mulat‐weldemeskel, Eyob
Abstract: Over the last decade, supply chain finance (SCF) has gained popularity and increasing attention among academicians and stakeholders in the context of financial flows in the supply chain. However, some research gaps still exist that need to be explored to improve the sustainability of supply chains. Specifically, there is a critical research need to look at the conceptual background of SCF and its potential applicability in various phases of supply chains. Therefore, this article aims to bridge this gap by conducting a comprehensive State‐of‐the‐Art literature review based on 367 papers published from 2006 to 2020. Furthermore, this article is one of the first attempts to present current and past studies in the domain of SCF in a holistic manner. The analysis highlights the most influential authors, keywords, organisations, leading publications and clusters in existing research areas. This article also sets out a proposed research framework based on the triangulation approach perspective, that is, financial perspective, buyer perspective and supply chain‐oriented perspective. The most important and unique contribution of the article is the identification of new and emerging research areas where the application of SCF is still in the nascent stage. These findings can guide stakeholders at every stage of the value chain to appropriately use techniques that model policies to better inform investment and operational decisions in line with Sustainable Development Goals.